국내의 토마토 주요 바이러스 진단을 위한 역전사중합반응법용 프라이머 세트 - 최홍수(Hong-soo Choi); 신준성(Jun-sung Shin); 한정헌(Jung-heon Han); 신유주(Yu-ju Shin); 곽해련(Hae-ryun Kwak); 김정수(Jeong-soo Kim) (Sigmulbyeong yeon'gu, 2017)
Major tomato viruses in Korea are Tomato chlorosis virus (ToCV), Tomato spotted wilt virus (TSWV), Cucumber mosaic virus (CMV), Pepper mottle virus (PepMoV), and Tomato mosaic virus (ToMV). RT-PCR conditions for the viruses were examined, especially in primer set and RT-PCR mixture. Total 46 primer sets from the unique sequence of the viruses were tested for nonspecific background products in a RT-PCR mixture without template. Among them 16 primer sets were applied to healthy tomato RNA, resulting the compatibility between RT-PCR mixture and primer set influenced RT-PCR to reduce nonspecific background products. Based on the combinations among cDNA synthesis parameters and RT-PCR mixtures, two reaction mixtures were finally selected for ToCV detection. The condition allowed to determine more specific primer sets; C029 (ToCV), C072 (TSWV), C070 (CMV), C048 (PepMoV), and C065 (ToMV). These primer sets are expected to be of use to specific detection of the major viruses in tomato plants. 국내의 토마토에서 발생하는 주요 바이러스는 Tomato chlorosis virus (ToCV), Tomato spotted wilt virus (TSWV), Cucumber mosaic virus (CMV), Pepper mottle virus (PepMoV), Tomato mosaic virus (ToMV)이다. 이들 바이러스를 진단하기 위해 프라이머 세트와 반응액을 포함하는 역전사중합반응(RT-PCR)법의 조건을 조사하였다. 공시한 바이러스에 특이적인 염기서열로부터 모두 46개 프라이머 세트를 설계하고, 이를 이용해 주형을 넣지 않은 RT-PCR에서 비특이 반응을 조사하였다. 이들 가운데 16개 조합을 건전한 토마토 RNA에 적용한 결과 프라이머 세트와 RT-PCR 반응액 간의 친화성이 비특이 반응 감소에 영향을 주었다. cDNA 합성과 관련된 인자와 RT-PCR 반응액 사이의 조합을 근거로 ToCV 진단을 위한 두 종류의 반응액을 선발하였다. ToCV 진단 시 수립된 조건을 나머지 바이러스 진단에 적용했을 때, 특이성이 높은 프라이머 세트 C029 (ToCV), C072 (TSWV), C070 (CMV), C048 (PepMoV), C065 (ToMV)를 선발할 수 있었다. 이들 프라이머 세트는 공시한 바이러스를 특이적으로 진단하는 데 유용할 것으로 판단된다.